1993
DOI: 10.1515/cclm.1993.31.5.303
|View full text |Cite
|
Sign up to set email alerts
|

A High-Performance Liquid Chromatographic Method for the Determination of Hypoxanthine, Xanthine, Uric Acid and Allantoin in Serum

Abstract: Summary: A method was developed for the simultaneous determination of hypoxanthine, xanthine, uric acid and allantoin based on isocratic reversed-phase chromatography. This HPLC-method additionally allows the direct determination with UV-detection of inosine-5'-phosphate, uridine, thymine, orotic acid, allopurinol and oxipurinol, besides hypoxanthine, xanthine and uric acid in the same Chromatographie run. Allantoin elutes in this system near the void volume and a fraction is collected covering the retention t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 8 publications
0
37
0
1
Order By: Relevance
“…11,[13][14][15] To avoid interferences in the sample matrices, many HPLC methods for the isolation and quantitation of creatinine, uric acid, and other metabolites in biological fluids have been described, including ion-exchange, normal-phase, reversed-phase, and reversed-phase ion-pair chromatography. [16][17][18][19][20][21] Reversed-phase HPLC methods with a highly aqueous mobile phase have been increasingly attractive in light of the recent movement of green analytical chemistry, which encourages the development of analytical methods without or with reduced consumption of organic solvent, energy and time. [17][18][19][22][23][24] However, many studies have reported that the use of a highly aqueous mobile phase (>90% water) with C18 and C8 columns causes an anomalous chromatographic behavior, and a retention loss of analytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,[13][14][15] To avoid interferences in the sample matrices, many HPLC methods for the isolation and quantitation of creatinine, uric acid, and other metabolites in biological fluids have been described, including ion-exchange, normal-phase, reversed-phase, and reversed-phase ion-pair chromatography. [16][17][18][19][20][21] Reversed-phase HPLC methods with a highly aqueous mobile phase have been increasingly attractive in light of the recent movement of green analytical chemistry, which encourages the development of analytical methods without or with reduced consumption of organic solvent, energy and time. [17][18][19][22][23][24] However, many studies have reported that the use of a highly aqueous mobile phase (>90% water) with C18 and C8 columns causes an anomalous chromatographic behavior, and a retention loss of analytes.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21] Reversed-phase HPLC methods with a highly aqueous mobile phase have been increasingly attractive in light of the recent movement of green analytical chemistry, which encourages the development of analytical methods without or with reduced consumption of organic solvent, energy and time. [17][18][19][22][23][24] However, many studies have reported that the use of a highly aqueous mobile phase (>90% water) with C18 and C8 columns causes an anomalous chromatographic behavior, and a retention loss of analytes. 19,25 These anomalies have been attributed to (i) aggregation of the bonded hydrocarbon chains in the presence of a highly aqueous mobile phase, rendering them inaccessible to analytes, and (ii) extrusion of the highly aqueous mobile phase from the pores of the particles of the stationary phase.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it is essential to develop a simple and rapid method for the separation and detection of these bioactive purine bases. Liquid chromatography (LC) [5][6][7][8][9] and capillary electrophoresis (CE) [10][11][12][13] have been widely used for the determination of purine bases and related compounds. To our knowledge, there are no reports on the use of CE microchips for the separation and detection of bioactive purines and related compounds.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore decided to reduce all ascorbate directly after sampling. Methodological difficulties in analyzing allantoin have resulted in a large number of methodological publications (32)(33)(34), none of which could be applied to our BAL samples.…”
mentioning
confidence: 99%